International Aid and Urban Change : Humanitarian Presence in Bamako, Abidjan, Nairobi and Juba. - de Roulet, Pablo (Bern : Peter Lang AG International Academic Publishers, 2022)
This work analyses the presence of humanitarian workers in African cities as a process of urban transformation. Humanitarian presence modifies the built environment and social relations. It results in development of economic activities targeted for expatriates while increasing an already unequal access to housing and privatisation of public space.
6.4.4 Fixers for Houses and Apartments -- 6.4.5 Hotel Employees -- 6.4.6 Balance of Salaries and Costs of Living -- 6.4.7 Service and Gendered Relationships -- 6.4.8 Rebuttals and Frictions -- Chapter 7 Transformations -- 7.1 Shaking Local Urban Economy -- 7.1.1 Local Employment -- The End of Direct Employment -- The Wide Variety of Indirect Employment and Businesses -- 7.1.2 Privatisation of Public Services -- Schools in Family Duty Stations -- Dual Health Services -- A Splintering of Public Services for the Future? -- 7.1.3 The Built Environment in the Local Economy -- Fears of Rent Increases -- Foreseeable Future for the Uses of a Renewed Built Environment -- 7.2 Control and Power in the Public Space -- 7.2.1 Road Blocks and Sand Bastions in the Street -- 7.2.2 The Radisson Hotel and the Levels of the State -- 7.2.3 Fragmented Upgrades in the Public Domain -- 7.2.4 Scales of Intervention -- 7.3 Aesthetics of Defensive Design -- 7.3.1 Spikes of All Sizes -- 7.3.2 Cars as Symbols -- 7.4 Outcomes in Abidjan -- Chapter 8 Synthesis -- Chapter 9 Conclusion -- List of Figures -- Bibliography.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books